ANALISIS USAHATANI SELADA HIDROPONIK SKALA RUMAH TANGGA DI KELURAHAN KAKASKASEN II KECAMATAN TOMOHON (Analysis of Household-Scale Hydroponic Lettuce Farming in Kakaskasen II Village, Tomohon Sub-District) - Kezia Grancya Manongko; Ellen G. Tangkere; Agnes E. Loho (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2023)
The purpose of this study is to analyze household-scale hydroponic lettuce farming in Ka-kaskasen II Village, Tomohon District. This research was conducted for 3 months from March to May 2022. The study location was in Kakaskasen II Village, Tomohon District. The data used in this study were primary and secondary data. Primary data were obtained through a questionnaire that had been prepared, and the respondents in this study were owners of hydroponic lettuce businesses in Kakaskasen II. Secondary data were obtained from related institutions and literature related to the study.Based on the processed hydroponic lettuce farming data, a revenue of Rp.3,393,966 was ob-tained, supported by an R/C Ratio value of 3.11, which means that for every Rp.1 expenditure, hy-droponic lettuce farming will generate revenue of Rp.3.11. Break Even Point analysis in this case can be seen from two sides, namely the production quantity/BEP (Q) and the selling price/BEP (Rp). Hydroponic lettuce farming in this study obtained (Q) of 7.6 and (Rp) of Rp.383,264.84, so hydro-ponic lettuce farming in Kakaskasen II is at the break-even point, where the farming does not make a profit but also does not incur a loss.